God"s patronage constitutes a community of compassionate equals - Malan, Gert J. (HTS teologiese studies, 2020)
The central themes of Jesus’ preaching, the kingdom and household of God, are root metaphors expressing the symbolic universe of God’s patronage subverting patronage and patriarchy structuring contemporary Mediterranean society, thus legitimising an anti-hierarchical community of faith. This dominant focus of Jesus’ message was discarded, as society’s prevalent patronage and patriarchy became the societal structure of the later faith communities. Today, patronage and patriarchy still forms the social structure for a large sector of Christian communities and many cultures, resulting in inequality, injustice, exploitation and suffering. This article proposes that the only remedy for the faithful is a return to Jesus’ essential message, by investigating the social dynamics suggested by these root metaphors using metaphor theory and social scientific methods. Patronage is studied within contemporary Roman and Mediterranean aristocratic patriarchal society, forming an a-typical broad-based needle-like power pyramid with multiple similarly structured power pyramids within, based on a morality of indebtedness, honour and power. Jesus accepted God as his father and declared the advent of God’s patronage as king (kingdom of God) and father of the faithful (children of God). Within the kingdom and household of God, there was no hierarchy, except for the primate of the first born son, whom Jesus symbolises as broker for God’s patronage to all his followers. Within the faith communities there should be no hierarchy or any form of clientage other than God’s patronage. Rather, the faithful are equal and should serve each other and their communities with compassion, responsibility and justice.Contribution: The contribution of this research is its focus on similarity and dissimilarity of these patronage metaphors and their application to subvert the power dynamics of patronage and patriarchy within the community of the faithful, in order to proffer God’s patronage of a society of caring, selfless equals today. This research falls within the scope of HTS Theological studies, as it is a multi-disciplinary study of key biblical metaphors investigated with accepted methodology resulting in valid conclusions which are ethically sound.